The Design and Validation of a Discrete-Event Simulator for Carbohydrate Metabolism in Humans - (:unkn) unknown (My University, 2020)
CarbMetSim is a discrete event simulator that tracks the changes of blood glucose level of a human subject after a timed series of diet and exercises activities. CarbMetSim implements wider aspects of carbohydrate metabolism in individuals to capture the average effect of various diet/exercise routines on the blood glucose level of diabetic patients. The simulator is implemented in an object-oriented paradigm, where key organs are represented as classes in the CarbMetSim. Key organs (stomach, intestine, portal vein, liver, kidney, muscles, adipose tissue, brain and heart) are implemented to the extent necessary to simulate their impact on the production and consumption of glucose. Metabolic pathways (glucose oxidation, glycolysis and gluconeogenesis) have been taken in account in the operation of various organs. In accordance with published research, the impact of insulin and insulin resistance on the operation of various organs/pathways is captured. CarbMetSim offers broad versatility to configure the insulin production ability, the average flux along various metabolic pathways and the impact of insulin resistance on different aspects of carbohydrate metabolism. However, the CarbMetSim project has not yet been finished. There are many aspects and metabolic pathways that have not been implemented or have been implemented in a simple manner. Also, additional validation is required before the simulator can be considered ready for use by people with Diabetes.